Determination and Comparison of the Amino Acid Composition of Seventeen Lagenaria siceraria Varieties and One Variety of Citrullus colocynthis Seed Flours - Sabo, Haoua; Sadou, Hassimi; Amoukou, Ibrahim Adamou; Alma, Mousbahou Malam; Sidikou, Ramatou Seini; Saadou, Mahamane; Suleman, Bilbis Lawal (Pakistan Journal of Nutrition, 2015)
Seeds from 17 varieties of Laganaria siceraria and 1 variety of Citrullus colocynthis were analyzed for their proximate amino acids composition. These seeds were produced on the Abdou Moumouni University, Faculty of Sciences and Technology, experimental field. The seeds showed significant difference in their protein content: Lagenaria siceraria (29.45 g/100 g), Citrullus colocynthis (12.40 g/100 g) but were closely related in their amino acids profile. Glutamic, aspartic acids and arginine were the most abundant amino acids while Total Sulphur Amino Acids (TSAA = methionine + cystine) were the limiting amino acids. Leucine was the most concentrated essential amino acid. The percentages of essential amino acids of the seeds were also closely related: Lagenaria siceraria (42.85%) and Citrullus colocynthis (41.51%). Despite a similar amino acids profile, the chemical concentrations of each amino acid were significantly different between varieties (p